Dimensions of Corporate Governance in Public Relations Literature: A Systematic Review - Pedja Ašanin Gole (Naše gospodarstvo/Our economy, 2024)
This article aims to uncover the dimensions or characteristics of corporate governance in the literature of public relations that are also related to communication. We employed a methodological approach based on a systematic review of scientific articles in the field of public relations using the PRISMA method, along with content analysis through axial coding, the use of the Atlas.ti tool, and meta-analysis. After reviewing two major online research databases, Science Direct and Emerald, we narrowed our search to Public Relations Review as the fundamental scientific journal in the field of public relations. We identified 19 communication dimensions of corporate governance, consolidating related concepts into ten. The originality of this research lies in identifying key communication dimensions of corporate governance as an institutional framework for public relations. The research results reinforce the significant role of communication even in the processes of institutionalizing corporate governance.